Effects of computerized visual feedback on the adjustment of time in planning physical education - López Walle, Jeanette M.; Viciana Ramírez, Jesús; Mayorga Vega, Daniel; Blanco Vega, Humberto; Ornelas Contreras, Martha; Tristán Rodríguez, José Leandro (2013)
The planning in Physical Education (PE) is a crucial competency of Pre-service Teachers (PTs) that is developing throughout the university courses. The adjustment of the time planned is a common problem for PTs without experience, and they show high differences between the time that they program and the real time that they employ during the intervention phase of teaching PE. We created a computerized time sheet to deliver visual feedback to PTs about this difference. Our aim was to accommodate quickly the adjustment of the time in planning in PE in a few sessions of visual feedback and coaching meeting with the supervisor of the faculty. We expose the computerized sheet and its application on one PT (an individual case) with a repeated measures series (three trials of baseline and ten trials of intervention were carried out). The results show us the efficacy of the computerized sheet (visual feedback and coaching meeting). We could verify the inflection of the curve since the first treatment trials, decreasing the differences between the time planned and the real time employed during the classes. We conclude that this method is a good way for PTs training during their university courses and for in-service teachers who want to improve their accuracy of planning PE in the future.